Analyzing Student Creative Thinking with Wallas Theory - Prabandari, Radha Sita; Nurhasanah, Farida; Siswanto, Siswanto (International Journal of Mathematics and Mathematics Education (IJMME), 2024)
Creative thinking can be influenced by students' learning styles, such as Field Independent (FI) and Field Dependent (FD) learning styles. This research aims to describe the creative thinking process of Field Independent learning style students in solving problems with higher-order thinking skills based on the Wallas stages. This qualitative study began by determining student’s learning styles using the Group Embedded Figure Test (GEFT) and then selecting three students with Field Independent (FI) learning styles. In this study, subjects with Field Dependent learning styles were excluded due to insufficient data collection. Data was collected using written tests and interviews and analyzed based on Wallas’s theory’s stages: preparation, incubation, illumination, and verification. Triangulation was used to validate the findings. The results show that students with Field Independent (FI) learning styles exhibit complete characteristics of creative thinking, including fluency, flexibility, and innovation, at every stage. This indicates their capability to think creatively in solving higher-order thinking problems.